Native Nanodiscs and the Convergence of Lipidomics, Metabolomics, Interactomics and Proteomics - Michael Overduin; Mansoore Esmaili (Applied Sciences, 2019)
The omics disciplines remain largely distinct sciences due to the necessity of separating molecular classes for different assays. For example, water-soluble and lipid bilayer-bound proteins and metabolites are usually studied separately. Nonetheless, it is at the interface between these sciences where biology happens. That is, lipid-interacting proteins typically recognize and transduce signals and regulate the flow of metabolites in the cell. Technologies are emerging to converge the omics. It is now possible to separate intact membrane:protein assemblies (memteins) directly from intact cells or cell membranes. Such complexes mediate complete metabolon, receptor, channel, and transporter functions. The use of poly(styrene-co-maleic acid) (SMA) copolymers has allowed their separation in a single step without any exposure to synthetic detergents or artificial lipids. This is a critical development as these agents typically strip away biological lipids, signals, and metabolites from their physiologically-relevant positions on proteins. The resulting SMA lipid particles (SMALPs) represent native nanodiscs that are suitable for elucidation of structures and interactions that occur in vivo. Compatible tools for resolving the contained memteins include X-ray diffraction (XRD), cryo-electron microscopy (cryoEM), mass spectrometry (MS), and nuclear magnetic resonance (NMR) spectroscopy. Recent progress shows that memteins are more representative than naked membrane proteins devoid of natural lipid and is driving the development of next generation polymers.